2022
DOI: 10.3390/biomedicines10123012
|View full text |Cite
|
Sign up to set email alerts
|

Stage- and Subfield-Associated Hippocampal miRNA Expression Patterns after Pilocarpine-Induced Status Epilepticus

Abstract: Objective: To investigate microRNA (miRNA) expression profiles before and after pilocarpine-induced status epilepticus (SE) in the cornu ammonis (CA) and dentated gyrus (DG) areas of the mouse hippocampus, and to predict the downstream proteins and related pathways based on bioinformatic analysis. Methods: An epileptic mouse model was established using a pilocarpine injection. Brain tissues from the CA and DG were collected separately for miRNA analysis. The miRNAs were extracted using a kit, and the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(73 reference statements)
1
0
0
Order By: Relevance
“…MiR-5106, which has been implicated in the healing process ( Xiong et al, 2020 ), was downregulated at both 1 and 8 h. MiR-7654-3p was downregulated at both 8 and 24 h, while miR-431-5 p exhibited upregulation at 24 h followed by downregulation at 120 h ( Xie et al, 2022 ). MiR-34b-5p , which has been linked to inflammation, apoptosis, and Parkinson’s disease in previous studies ( Liu et al, 2016 ; Xie et al, 2018 ; Li et al, 2020 ; Xie et al, 2022 ) showed changes in expression levels at all stages, with upregulation at early stages and downregulation at 120 h ( Figure 5B ), similar to another recent SE study ( Li et al, 2022 ). It will be interesting to investigate specific biological significance of miR-34b-5p in this mouse model of TLE and this could be fruitful future direction for study.…”
Section: Resultssupporting
confidence: 87%
“…MiR-5106, which has been implicated in the healing process ( Xiong et al, 2020 ), was downregulated at both 1 and 8 h. MiR-7654-3p was downregulated at both 8 and 24 h, while miR-431-5 p exhibited upregulation at 24 h followed by downregulation at 120 h ( Xie et al, 2022 ). MiR-34b-5p , which has been linked to inflammation, apoptosis, and Parkinson’s disease in previous studies ( Liu et al, 2016 ; Xie et al, 2018 ; Li et al, 2020 ; Xie et al, 2022 ) showed changes in expression levels at all stages, with upregulation at early stages and downregulation at 120 h ( Figure 5B ), similar to another recent SE study ( Li et al, 2022 ). It will be interesting to investigate specific biological significance of miR-34b-5p in this mouse model of TLE and this could be fruitful future direction for study.…”
Section: Resultssupporting
confidence: 87%